2007
DOI: 10.1375/acri.40.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Education, Employment Destinations, and Graduate Satisfaction

Abstract: The article addresses the lack of sound empirical research both overseas and especially in Australia on the outcomes of criminal justice education. The very limited research on graduate outcomes is potentially problematic at a time when governments are increasingly calling for program accountability and evaluation in higher education. The article reports on an empirical study of one criminology/criminal justice program that investigated the employment destinations of graduates. Principal components analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It should also be noted that the name and content of criminology degrees is culturally and historically specific. For example, Wimshurst and Ransley (2007) describe the introduction of policing-oriented degrees in Queensland following the Fitzgerald Inquiry (see also Wimshurst & Allard, 2007). In this paper, we have sought to map criminal justice education in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that the name and content of criminology degrees is culturally and historically specific. For example, Wimshurst and Ransley (2007) describe the introduction of policing-oriented degrees in Queensland following the Fitzgerald Inquiry (see also Wimshurst & Allard, 2007). In this paper, we have sought to map criminal justice education in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Australian research of the teaching of research methods has shown that these types of courses are widely taught within undergraduate criminology degrees (Bartels et al, 2015) and that the vast majority (80%) of graduates self-report that their degree helped develop their research skills (Wimshurst & Allard, 2007). Nevertheless, while research methods are widely taught as core component of Australian criminology degrees, courses specifically educating students about data analysis (both quantitative and qualitative) are not taught as widely across all Australian degrees (Bartels et al, 2015).…”
Section: Extent Of Research Methods Training In Criminology Degreesmentioning
confidence: 99%
“…It may be that in another research context, perhaps addressing specifically the relationship between viewing preferences and careers, our 20 participants might have had more to say about contemporary crime, but not during the current research. The participants touched on career plans, but not as much as we might expect, given both the ubiquity of crime drama as well as the strong vocational orientations of criminology students (Tontodonato, 2006;Wimshurst and Allard, 2007).…”
Section: Crime Drama and Professional Identitiesmentioning
confidence: 99%